The role of inflammation markers in predicting the prognosis of Bell’s palsy - Ulusoy, Bülent; Bozdemir, Kazım; Kale, Hayati; Korkmaz, Mehmet Hakan (The European Research Journal, 2019)
Objectives: This study aimed to investigate the relationship between the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) and Bell’s palsy in addition to the usability of these markers to predict prognosis. Methods: In this prospective study, the patient group included 24 patients that were diagnosed with Bell’s palsy and 29 healthy volunteers that had similar characteristics to them regarding age and gender with patient group as the control group. The temporal gadolinium-enhanced magnetic resonance imaging (TGd-MRI) was performed to all patients. The complete blood count was also obtained from both the patient and the control groups, and these two groups were compared for NLR and PLR, mean platelet volume (MPV), platelet distribution width (PDW), and platelet count. The relationship between these markers and Bell’s paralysis prognosis was also investigated. Results: The patient and control groups were similar in age and gender (p > 0.05). NLR was significantly higher in the patient group compared with the control group (p = 0.016). There was no correlation between the NLR value and the prognosis of Bell’s Palsy. The PDW and white blood cell count (WBC) were significantly higher in the patient group than the control group (p = 0.023 and p = 0.012, respectively). A comparison of the recovered and unrecovered patients revealed that the PDW value was significantly higher and the platelet count was lower in the recovered patients than the unrecovered patients (p = 0.009 and p = 0.003 respectively). The MPV value was higher in the recovered patients, though not statistically significant (p = 0.063). Based on the cut-off values determined in the receiver operator characteristic (ROC) curve analysis, a comparison of the recovered and unrecovered patients reveals that the likelihood of not healing was significantly higher in those that had normal PDW values (p = 0.036).